Midwifery Now: Narratives about Motivations for Career Choice - Margarida Sim-Sim; Otília Zangão; Maria Barros; Ana Frias; Hélia Dias; Anabela Santos; Vicki Aaberg (MDPI AG, 2022)
The objective of this study was to analyse nursing students' motivation to choose the midwifery career. This is a cross-sectional study with a qualitatively driven mixed-methods approach. The settings are three higher education institutions located in Portugal. The study was conducted between September 2019 and November 2021, with the participation of 74 midwifery master's students, through convenience sampling. The data were collected through the LimeSurvey software and were subsequently analysed in the SPSS and IRaMuTeQ software programs. The emerging thematic areas were as follows: (1) building a professional identity and (2) knowledge construction. From these two thematic areas, six classes emerged that revealed commitment to the profession. It is in Class 6 that the ancestral essence of the profession lies, revealing the meanings of competence and care perpetuation linked to gender. Midwifery is a first-line profession, and the career choice reflects a commitment to support the mother/newborn dyad in view of the inevitability of human care for the preservation of the species. Midwives with a Socratic inspiration are the model for the profession. Given the development of professional identity, it can be interesting to have an educational curriculum where human values are reinforced. A woman-centred birth environment and birth territory are elementary for midwifery education.